Análise da Produção Escrita em provas de Cálculo Diferencial e Integral I - Bortoletto, Diovanna (2021)
The research theme, which is of interest to Mathematics Education, is part of the teaching of Differential and Integral Calculus I (CDI1). This is a qualitative research of an interpretive nature based on Content Analysis, developed from a group of 58 students who have recently entered an Engineering course and enrolled in CDI1, with the following question: what do the written productions of students, in a question of the first test of the Differential and Integral Calculus course of a Civil Engineering course, reveal about the way they deal with Mathematics? Therefore, assessment is considered as a research practice to identify the way students deal with Mathematics. The objective is to present how the students' written productions, in tests of the Differential and Integral Calculus I discipline, can lead to the elaboration of tasks. From the understanding of their listed knowledge, some tasks, from the perspective of the analysis of written production, were directed to them, to assist in the teaching and learning process and be subsidies to reorient the teaching practice in progress, as well as subsidize future courses in Differential and Integral Calculus. Among the theoretical aspects that approach this problem, the one chosen was Realistic Mathematics Education. More specifically, the concept of Guided Reinvention was listed to guide the study. The written productions of students entering an Engineering course, from the discipline of Calculus I, in a situation of evaluation, served as instruments for collecting information about student learning. The productions revealed that students need monitoring and activities of progressive levels, which are focused on their realities, so that they remember or have knowledge of basic mathematics that will be used in the knowledge covered at the beginning of academic life. Finally, some tasks focused on the reality found, were directed to the students of the course, and left as a suggestion for a future course, to assist in the teaching and learning processes and obtain subsidies to reorient the current teaching practice and subsidize other courses of Differential and Integral Calculus.